2021
DOI: 10.1287/mnsc.2020.3718
|View full text |Cite
|
Sign up to set email alerts
|

Information Transparency, Multihoming, and Platform Competition: A Natural Experiment in the Daily Deals Market

Abstract: Platform competition is shaped by the likelihood of multihoming (i.e., complementors or consumers adopt more than one platform). To take advantage of multihoming, platform firms often attempt to motivate their rivals’ high-performing complementors to adopt their own platforms, or they attempt to prevent their current complementors or consumers from multihoming. In this paper, we study the effectiveness of such strategies in the context of the online daily deals market. We first develop a game-theoretical model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 42 publications
0
35
0
2
Order By: Relevance
“…Previous studies have reported that information transparency can reduce information asymmetry between consumers and sellers, improve consumer trust, and promote purchase behaviors (Kraft et al, 2020;Mohan et al, 2020). However, in practice, information transparency is a doubleedged sword (Zhu, 2004), and sellers may not always benefit from it (Zhu, 2002;Li and Zhu, 2021). Therefore, further exploration of the mechanisms through which information transparency affects consumer purchase behavior is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that information transparency can reduce information asymmetry between consumers and sellers, improve consumer trust, and promote purchase behaviors (Kraft et al, 2020;Mohan et al, 2020). However, in practice, information transparency is a doubleedged sword (Zhu, 2004), and sellers may not always benefit from it (Zhu, 2002;Li and Zhu, 2021). Therefore, further exploration of the mechanisms through which information transparency affects consumer purchase behavior is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…We re-classified the level of enterprise information transparency. 75% of enterprise information transparency level was delimited, as shown in Table 9 (Li & Zhu, 2021 ). After replacing the classification method of enterprise information transparency, we found that the results were still significant, indicating the robustness of the results.…”
Section: Robustness Testmentioning
confidence: 99%
“…Many platforms are information transparent to the complementors to enhance the consumers’ trust, like ratings and sales information. Li & Zhu ( 2021 ) study the competition in platform operations, which is caused by multi-homing. The analysis emphasizes the influence of information transparency on consumers, rival firms, and the industry empirically, and indicates that limiting information transparency helps reducing multi-homing.…”
Section: Review Of Related Studiesmentioning
confidence: 99%